Analysis of Socio-Economic Characteristics and Utilization of Healthcare Facilities in Owo Local Government Area of Ondo State, Nigeria - Olugbamila, Omotayo Ben; Adeyinka, Samson Ajibola (European Scientific Journal, ESJ, 2017)
This paper examines the socio-economic characteristics of residents and their utilization of available healthcare facilities in Owo local government area of Ondo State, Nigeria. The data utilized in the paper draws on systematic sampling of 368 health consumers in the study area. Findings revealed that socio-economic characteristics play a significant role in determining the frequency of visits to healthcare facilities, this is substantiated with the chi-square test result that revealed a significant relationship between marital status and frequency of visits to healthcare facilities with Ï‡Â² = 29.175 and significant at p = 0.004 level, as well as income of households and the frequency of visits to healthcare facilities with Ï‡Â² = 20.961 and significant at p = 0.007 levels. The paper therefore concluded that efforts should be put in place to improve the socio-economic status of individuals through multi-sectoral development activities such as micro-credit facilities and provision of employment opportunities which is believed will invariably improve their access and utilization of healthcare facilities.